SUCH FORMS AND METHODS OF MOTIVATION OF PRACTITIONERS IN THE SPHERE OF YOUR EDUCATION - KOZYNETS, Anatolii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
It is important to create a modern management system capable of responding to dynamic changes in the outside world. This system should include taking into account the internal resources and needs of the institution. It is also important to develop educational and scientific processes in which employees can actively participate. This is vital, as the effectiveness of the functions of higher education institutions depends on it. The competitiveness of the higher educational institution of the company providing educational services is ensured by qualified innovative employees of the institution. This is due to the fact that most of the managerial responsibilities of higher education institutions involve the appointment of employees who meet the established requirements for their positions; assessment of their efficiency as employees; motivation and remuneration of employees. The motivation of employees to improve the quality of the work of teachers and scientists is one of the key components of the development of a higher educational institution. The purposeof the study is to study the functional features of management of the motivation of employees of higher education institutions. The results.The specificity of the activities of scientific and pedagogical workers is characterized by a creative, research, innovative nature, which has an educational and communicative focus. Therefore, taking into account the creative motives of behavior is important for the effective management of a higher educational institution. The innovative focus of work involves the use of the latest information technology tools, communication channels and educational platforms. Management of motivation for the development of professional competence of scientific and pedagogical workers is based on adherence to a person-oriented approach. The factor of remuneration as one of the material means of motivation is effective if it performs not only a reproductive, but also a stimulating function. Therefore, in order to encourage highly qualified employees to work for many years in an educational institution, it is necessary to provide them with a competitive salary. Material rewards for high achievements in work should exceed the amount of compensation for the costs of educational and scientific activities in order to stimulate employees to further realize their own scientific and teaching potential. An important component of the motivational system is the style of management, according to which the interests of employees are prioritized for the needs of the higher educational institution, therefore management is aimed at harmonizing personal and organizational interests. Having satisfied the need for optimal working conditions, the employee seeks to satisfy higher needs, in particular, the need for recognition. Therefore, the determining aspect of motivation management in a higher educational institution should be the proportional dependence of the motivational reward (material or non-material) on the efforts made by the employee to achieve performance results. In the modern management of a higher education institution, it is important to use motivation as one of the effective ways to ensure personnel potential. By carrying out systematic measures of internal and external management motivation, the higher educational institution not only attracts highly qualified employees, but also ensures their interest in effective work in the institution. Effective management of labor motivation requires a complex, flexible and open system of labor motivation management. This is due to the fact that a flexible and open system is needed to harmonize and optimize the needs of both the teaching and research staff and the higher education institution. It is also necessary to achieve mutually beneficial development goals. Effective management of motivation is based on the creation of a wide range of intangible and tangible motivational tools. This helps higher education institutions to compete with other educational services in domestic and international markets. The creation of a flexible and complex system requires the creation of additional types of activities.